Potential applications of PET/MRI in non-oncologic conditions within the abdomen and pelvis. - Bartlett, David J.; Takahashi, Hiroaki; Bach, Corrie R.; Lunn, Brendan; Thorpe, Matthew P.; Broski, Stephen M.; Packard, Ann T.; Fletcher, Joel G.; Navin, Patrick J. (Abdominal Radiology, 2023)
PET/MRI is a relatively new imaging modality with several advantages over PET/CT that promise to improve imaging of the abdomen and pelvis for specific diagnostic tasks by combining the superior soft tissue characterization of MRI with the functional information acquired from PET. PET/MRI has an established role in staging and response assessment of multiple abdominopelvic malignancies, but the modality is not yet established for non-oncologic conditions of the abdomen and pelvis. In this review, potential applications of PET/MRI for non-oncologic conditions of abdomen and pelvis are outlined, and the available literature is reviewed to highlight promising areas for further research and translation into clinical practice.